Correction: Tolpeznikaite et al. Characterization of Macro- and Microalgae Extracts Bioactive Compounds and Micro- and Macroelements Transition from Algae to Extract. Foods 2021, 10, 2226 - Ernesta Tolpeznikaite; Vadims Bartkevics; Modestas Ruzauskas; Renata Pilkaityte; Pranas Viskelis; Dalia Urbonaviciene; Paulina Zavistanaviciute; Egle Zokaityte; Romas Ruibys; Elena Bartkiene (Foods)
In the original publication [...]